SOCIO-CULTURAL DYNAMICS OF ROMANIAN THROUGH THE LENS OF RL2 LEARNERS - Anamaria RADU; Alexandra COTOC (Studia Universitatis Babeş-Bolyai. Philologia)
Socio-cultural Dynamics of Romanian through the Lens of RL2 Learners. This research investigates the social and cultural dynamics of the Romanian language, with a particular emphasis on its status as a prestige language within the RL2 learner communities. Using a mixed-methods research design, the study combines quantitative data with qualitative data obtained from observations and a questionnaire addressed to RL2 learners. Shifting the role played by the Romanian language from being a ‘minor’ language to being a prestige language within an RL2 community of practice through cultural immersion underscores the significance of social interactions in the language learning process. By offering a detailed understanding of the Romanian language within its cultural milieu, this study seeks to contribute to the portrayal of the RL2 learner profile.